Adhesive wear performance of tungsten carbide based solid lubricant material. (September 2015) - Muthuraja, A.; Senthilvelan, S.
Abstract: In this work, adhesive wear performance of the developed tungsten carbide based solid lubricant material is presented. In-house developed materials were evaluated for the sliding wear performance against the commercial tungsten carbide disc. Removal of cobalt binder in the sintered material is identified as the major surface failure mechanism under adhesive wear condition. The formation of the transfer layer on the counter material during adhesive wear is confirmed with the aid of non-contact profiler. Soft phase calcium fluoride formed a bulky transfer layer on the counter disc which resulted in the reduction of friction and wear. In spite of similar frictional force, wear loss was found to be less when compared to that of abrasive condition. The measured net surface temperature of the test specimen also confirmed that tungsten carbide with calcium fluoride exhibited less friction. Wear tracks obtained after scratch resistance test confirmed that WC with 5% CaF2 material exhibited shallow and wide wear track. However, tungsten carbide without calcium fluoride material exhibited deep and narrow wear track. Highlights: Tungsten carbide based solid lubricant cutting tool material was evaluated for the adhesive wear performance. Removal of bonding material, cobalt was identified as the primary wear mechanism in the sliding wear performance test material. Calcium fluoride was extruded from the test material during sliding and reduces friction and wear. Narrow and deep scratches confirmed the poor bonding between carbide particles while scratch resistance evaluation.